Survival and Stationary Distribution in a Stochastic SIS Model - Yanli Zhou; Weiguo Zhang; Sanling Yuan (Discrete Dynamics in Nature and Society)
The dynamics of a stochastic SIS epidemic model is investigated. First, we show that the system admits a unique positive global solution starting from the positive initial value. Then, the long-term asymptotic behavior of the model is studied: when R0≤1, we show how the solution spirals around the disease-free equilibrium of deterministic system under some conditions; when R0>1, we show that the stochastic model has a stationary distribution under certain parametric restrictions. In particular, we show that random effects may lead the disease to extinction in scenarios where the deterministic model predicts persistence. Finally, numerical simulations are carried out to illustrate the theoretical results.